Electron beam and RF wave interaction mechanism in the reltron oscillator - Mahto M.; Jain P.K. (My University, 2025)
Reltron is simple, compact and efficient high power microwave source. In this paper, the beam-wave interaction analysis of the reltron device has been explained. To investigate the electron beam and RF wave interaction process, 3D PIC simulation of the device has been carried out in the presence of the electrons emitted through the cathode. For the typical reltron device considered here, the present simulation study predicted a peak RF power of ∼120MW at 2.75 GHz with an electronic efficiency of ∼23% when a beam voltage of 100 kV, post-acceleration voltage of 600 kV and beam current of 750 A are applied. This has been found in the close agreement with the analytical results within ∼4-9%. © 2016 IEEE.